Improving the method of linear-quadratic control over a physical model of vessel with azimuthal thrusters - Budashko, Vitalii; Sandler, Albert; Khniunin, Sergii (Eastern-European Journal of Enterprise Technologies, 2023)
The object of this research is the algorithms for controlling large-scale models of sea-based vehicles (SBVs). The subject of the research is a linear-quadratic method for controlling a model of the propulsion complex with azimuthal thrusters (ATs) in the aft part. The problem is the solution between the interdependent throws of surge, sway, and yaw speeds predicted by the linear controller. Input signals are the rotational speeds and the angles of ATs propeller thrusts with respect to the diametrical plane of SBVs. During the simulation, step responses of a closed system for overload and rotation speed are compared. Simulation of speed jumps showed an adequate response, in contrast to the speed of rotation of ATs, which showed a greater impact on the system than the orientation of ATs. When modeling the rate of yaw, the behavior of the ATs angle did not correspond to its limitations inherent in the device rotating at the appropriate speed. It is concluded that this is the result of linearization of the actuators, and the proposed solution is to implement the strengthening of the task to better adapt to the rotating behavior of ATs. Despite these problems, the simulation showed the potential of the model and controller for use in similar situations. Several modifications are also offered to significantly improve the model and simulations. One of the main changes that could be made is the implementation of a predictive gain during the linearization of the ATs control system. The practical significance of the results obtained is the fact that the quadratic optimization model is an effective and reliable technique in the process of designing SBVs of various configurations of steering devices for optimal control